Modern Hypertext Poetry: Aspects of Relations between Author’s Text and In-ternet Resources - E. A. Abrosimova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The article is devoted to the referential relations between the author’s text and Internet resources in modern hypertext poetry. The relevance of the research is related to the general interest of philology in intermediate phenomena, the increasing role of Internet communication in poetic discourse, and the introduction of elements of digital culture into the poetic language. The novelty is seen in the appeal to currently little-studied non-utilitarian hypertext works. Aspects of research of referential relations between a verbal text and network resources in  relation to a literary text are defined. The research material was poems, cycles of poems, books of modern poets that contain links that the reader can use to make the transition to the continuation / addition of the text on the Internet. The following aspects of the analysis are highlighted: the location and form of the hyperlink, the range of the hypertext “jump,” the type and genre of the media “target,” the state of the resource to which the link leads, the degree of immersion of the recipient in the hypertext structure. Examples of implementation of  hypertext transitions are analyzed, conclusions are drawn about the expressive possibilities of hyperlink organization of works of poetic discourse.